2020
DOI: 10.1039/c9sc05335b
|View full text |Cite
|
Sign up to set email alerts
|

Selenophosphoramide-catalyzed diamination and oxyamination of alkenes

Abstract: Scavenging fluoride from a selenophosphoramide-catalyzed alkene oxidation reaction suppresses the known syn-elimination pathway, enabling alkene diamination/oxyamination reactions via substitution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 40 publications
0
7
0
2
Order By: Relevance
“…In a similar manner, analogous complexes of these ligands with selenium, i.e., phosphine selenides and selenoureas, which are trivial to generate from the corresponding phosphines and imidazolium salts, might also serve as more effective catalysts. Indeed, we and others have recently shown that these complexes can be used to control the selectivity of selenium-catalyzed reactions. Gratifyingly, phosphine selenide catalysts did afford the desired allylic amination product, with 15 mol % tricyclohexylphosphine selenide (Cy 3 PSe) proving to be the most convenient and effective catalyst. The quantity of catalyst could be reduced further to 5 mol % with only a moderate drop in yield.…”
Section: Resultsmentioning
confidence: 99%
“…In a similar manner, analogous complexes of these ligands with selenium, i.e., phosphine selenides and selenoureas, which are trivial to generate from the corresponding phosphines and imidazolium salts, might also serve as more effective catalysts. Indeed, we and others have recently shown that these complexes can be used to control the selectivity of selenium-catalyzed reactions. Gratifyingly, phosphine selenide catalysts did afford the desired allylic amination product, with 15 mol % tricyclohexylphosphine selenide (Cy 3 PSe) proving to be the most convenient and effective catalyst. The quantity of catalyst could be reduced further to 5 mol % with only a moderate drop in yield.…”
Section: Resultsmentioning
confidence: 99%
“…23,24 In addition, Michael and co-workers found that a selenophosphoramide can generate a seleniranium ion catalytically, while also acting as a good leaving group for a secondary nucleophilic addition (Scheme 3e). 26 This method comprises several examples using unsaturated esters and sulfonimides for the formation of racemic 1,2-amino alcohol precursors in fair to good yields. Interestingly, this method was disclosed as a serendipitous discovery within the context of an alkene diamination investigation.…”
Section: ■ Backgroundmentioning
confidence: 99%
“…Kürzlich haben Denmark und Mitarbeitende sowie Michael und Mitarbeitende dieses Konzept erweitert, indem sie katalytische Methoden entwarfen, die jeweils eine direkte und teilweise asymmetrische syn ‐1,2‐Dichlorierung, syn ‐1,2‐Oxylierung oder syn ‐ bzw. anti ‐1,2‐Diaminierung von Alkenen ermöglichten [14–17] …”
Section: Introductionunclassified